If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 4) = 5 * 3 Reorder the terms: 2(4 + x) = 5 * 3 (4 * 2 + x * 2) = 5 * 3 (8 + 2x) = 5 * 3 Multiply 5 * 3 8 + 2x = 15 Solving 8 + 2x = 15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 2x = 15 + -8 Combine like terms: 8 + -8 = 0 0 + 2x = 15 + -8 2x = 15 + -8 Combine like terms: 15 + -8 = 7 2x = 7 Divide each side by '2'. x = 3.5 Simplifying x = 3.5
| 6/5=12/v+7 | | 3u/18=15 | | 3/4=v-4/10 | | 1x-1y+6z= | | 5x-3y-7z= | | 5/7=6/v | | 13/y=7/17 | | 8x-4y-1z= | | d/5+10=d-14 | | y/13=8/11 | | 13-7x=165-35x | | 243+100=7x | | 6(v+3)=-2(2v-7)+2v | | 8(-0.625)+9= | | -8.1q+1.6=-59.6-1.3q | | -11+8=x | | y=x-2/5 | | 2775000+20000x=5000000 | | 4/5*t-3=5 | | 7n=8n-(-11) | | 9x-3x=-42 | | 5000000=31250x | | 4r/7=12 | | 2c+5=17 | | 3(4x-7)-4x=5 | | 9b=-99 | | (4x+7)/(x+1) | | 1/15(d)=1/5 | | -7/2w+3=-7/6w-4/3 | | 4y-(y-13)=y+9 | | 2(4x-5)=4(2x-3)+2 | | 7/3v-1/2=-7/4v+7 |